Age of first concussion and cognitive, psychological, and physical outcomes in NCAA collegiate student athletes - Moody, J. N.; Hayes, J. P.; Buckley, T. A.; Schmidt, J. D.; Broglio, S. P.; McAllister, T. W.; McCrea, M.; Pasquina, P. F.; Caccese, J. B.; CARE Consortium Investigators (Sports Medicine, 2022)
Objective: Concussions are common among youth athletes and could disrupt critical neurodevelopment. This study examined the association between age of first concussion (AFC) and neurocognitive performance, psychological distress, postural stability, and symptoms commonly associated with concussion in healthy collegiate men and women student athletes. Methods: Participants included 4267 collegiate athletes from various contact, limited-contact, and non-contact sports (1818 women and 2449 men) who completed baseline assessments as part of the Concussion Assessment, Research and Education (CARE) Consortium. Psychological distress was assessed with the Brief Symptom Inventory 18; neurocognitive performance was assessed with the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT); symptoms commonly associated with concussion were assessed with the ImPACT Post-Concussion Symptom Scale; postural stability was assessed with the Balance Error Scoring System. Generalized linear models were used to examine the effects of AFC on clinical outcomes separately in men and women. Results: Later AFC was associated with lower global (Exp(B) = 0.96, P = 0.001) and somatic (Exp(B) = 0.96, P = 0.002) psychological distress on the Brief Symptom Inventory 18 and faster ImPACT reaction time (B = - 0.003, P = 0.001) in women. AFC was not associated with any clinical outcomes in men. Conclusion: Younger AFC was associated with some differences in psychological distress and reaction time among women but not men; however, these results are likely not clinically meaningful. Sociodemographic disparities, pre-existing conditions, and sport type may impact clinical and cognitive outcomes in collegiate athletes more than concussion history. Future work should examine the relationship between AFC and lifespan-related outcomes.